European map of prevalence rates of elder abuse and its impact for future research - Donder, Liesbeth de (2011)
This article aims to map existing prevalence research on abuse and neglect of older people and to provide a critical overview of existing methodologies, which have been adopted to survey the prevalence rates of abuse against elders. This article is part of the prevalence study of Abuse and Violence against Older Women (AVOW) study, which was conducted in five European countries (Austria, Belgium, Finland, Lithuania, and Portugal). The article provides an overview of the state of the art of prevalence data, survey designs and methods, instruments and results in Europe. Therefore, this draws on an extensive literature search and qualitative content analysis, which was conducted as an early part of the AVOW study. Results indicate that some EU countries have a rich history of prevalence research, whereas other countries have just begun to tackle this aspect of research on of elder abuse. One of the lacunae concerns reliable numbers on the prevalence rates of elder abuse. Research about where, when and how often elder abuse occurs, is inadequate and inconsistent. Data in some cases are based on professionals’ reports rather than on information from older people themselves. Surveying elders about such a sensitive topic, however, implies the need for an adequate research instrument (questionnaire) and research design, and an adapted data collection method. In conclusion, substantial attention is paid to outlining possible guidelines for future research.